2013
DOI: 10.1007/s11999-013-3232-z
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Opioid Administration Inhibits Bone Healing in an Animal Model

Abstract: Background The current mainstay of orthopaedic pain control is opioid analgesics but there are few studies in the literature evaluating the effects of opioids on bone healing. Questions/purposes The purpose of this study was to use a rat fracture model to evaluate the effects of opioid administration on osseous union in the acute (4 weeks) and subacute (8 weeks) setting in an operatively stabilized fracture. We asked the following question: does morphine administration alter (1) fracture callus strength; (2) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 13 publications
0
36
0
1
Order By: Relevance
“…Pro [32] NSAID use at admission Pro [13,27] Con [17,35] NSAID use at discharge Pro [13,27] Con [17,35] Opioid use at admission Pro [12] Opioid use at discharge Pro [12] Human immunodeficiency virus Pro [24] Con [20] Hepatitis C None Diabetes Pro [13,21,27] ASA score Pro [16] Smoking status Pro [13,21,31,36] Con [29,35] Alcohol use Pro [10,13,21] AO classification Pro [30] Con [2,22] ISS score Pro [30] TRISS score Pro [30] ICU days None * Pro articles support a correlation between nonunion and the variable; Con articles show that the variable has no correlation with nonunion; GSW = gunshot wound; NSAID = nonsteroidal anti-inflammatory drug; ASA = American Society of Anesthesiologists; AO = Arbeitsgemeinschaft für Osteosynthesefragen; ISS = Injury Severity Score; TRISS = Trauma and Injury Severity Score; ICU = intensive care unit.…”
Section: Compartment Syndromementioning
confidence: 99%
“…Pro [32] NSAID use at admission Pro [13,27] Con [17,35] NSAID use at discharge Pro [13,27] Con [17,35] Opioid use at admission Pro [12] Opioid use at discharge Pro [12] Human immunodeficiency virus Pro [24] Con [20] Hepatitis C None Diabetes Pro [13,21,27] ASA score Pro [16] Smoking status Pro [13,21,31,36] Con [29,35] Alcohol use Pro [10,13,21] AO classification Pro [30] Con [2,22] ISS score Pro [30] TRISS score Pro [30] ICU days None * Pro articles support a correlation between nonunion and the variable; Con articles show that the variable has no correlation with nonunion; GSW = gunshot wound; NSAID = nonsteroidal anti-inflammatory drug; ASA = American Society of Anesthesiologists; AO = Arbeitsgemeinschaft für Osteosynthesefragen; ISS = Injury Severity Score; TRISS = Trauma and Injury Severity Score; ICU = intensive care unit.…”
Section: Compartment Syndromementioning
confidence: 99%
“…Previous studies have investigated the medication influence on the callus formation and remodeling stages of bone fracture (13,14), while the influence of FCE on the acute stage of fracture is seldom studied. People who suffer from traumatic fracture are often admitted for further surgery, medical care of soft tissue, and administration of analgesics (1).…”
Section: Discussionmentioning
confidence: 99%
“…Biomechanical testing and micro-CT analysis expressed that morphine administration leads to weaker callus and impedes callus maturation compared with controls. These fi ndings may change the post-op Orthopaedic analgaesic regimens [ 10 ]. Demirtas et al showed that Enoxaparin, Fondaparinux and Rivaroxaban used in thromboembolism prophylaxis caused no signifi cant changes in fracture healing in terms of clinical, radiological, and histopathological fi ndings with short term follow-up (21 days) in a standard closed femur fracture model in rats [ 11 ].…”
Section: New Signalling Pathways and Treatment Modalitiesmentioning
confidence: 99%
“…Cartilage cells (harvested from the talus of horses) were cultured and transduced with 10 5 AAV vg/cell prior to implantation. Arthroscopically created 15 mm full-thickness chondral defects were fi lled with naïve or gene-enhanced chondrocytes, in fi brin.…”
Section: New Treatment Modalities and Growth Factorsmentioning
confidence: 99%